2010
DOI: 10.1074/jbc.m109.036343
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Activation Is Essential to Induce a Th1 Shift in Human Peripheral Blood Mononuclear Cells by Plant Stanols and Plant Sterols

Abstract: Plant sterols may induce a Th1 shift in humans. However, whether plant stanols have similar effects as well as the underlying mechanism are unknown. We have now shown that (like sitosterol) sitostanol, both 4-desmethylsterols, induces a Th1 shift when added in vitro at physiological concentrations to human PBMCs. This conclusion was based on a higher IFN␥ production, with no change in the production of IL-4 and IL-10. ␣-Amyrin, a 4.4-dimethylsterol, had comparable effects. Because 4.4-dimethylsterols cannot ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
(45 reference statements)
4
32
0
Order By: Relevance
“…In this disease, driving Th1 or Th2 responses correlates with the severity of the fungal infection and Th1-type dominance can reduce severity. Finally, Brull et al [32] demonstrated that sitosterol is able to shift immunity towards a Th1 dominant response in humans, at least ex vivo, and this effect is a plant sterol specific one and not a sterol effect in general. Moreover, they clearly demonstrated that TLR2 activation was essential to induce this Th1 shift in human PBMCs by plant stanols and plant sterols.…”
Section: Discussionmentioning
confidence: 95%
“…In this disease, driving Th1 or Th2 responses correlates with the severity of the fungal infection and Th1-type dominance can reduce severity. Finally, Brull et al [32] demonstrated that sitosterol is able to shift immunity towards a Th1 dominant response in humans, at least ex vivo, and this effect is a plant sterol specific one and not a sterol effect in general. Moreover, they clearly demonstrated that TLR2 activation was essential to induce this Th1 shift in human PBMCs by plant stanols and plant sterols.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, both nonmodified and modified phytosterols suppress an inflammatory transcriptional profile in macrophages [42,[182][183][184][185][186][187][188]. Furthermore, plant sterols and plant stanols skew T cells toward a Th1 phenotype independently of their effect of antigen-presenting cells (APCs) and leaving the activity of Th2 cells unaffected [180,189,190]. With respect to MS, sitosterol has been reported to decrease the secretion of the inflammatory mediators TNFa and IL-12 by PBMCs from MS patients at physiological relevant concentrations [181].…”
Section: Phytosterols In Multiple Sclerosismentioning
confidence: 97%
“…Numerous studies have reported immunomodulatory properties of phytosterols [38,42,114,[180][181][182][183]. For instance, both nonmodified and modified phytosterols suppress an inflammatory transcriptional profile in macrophages [42,[182][183][184][185][186][187][188].…”
Section: Phytosterols In Multiple Sclerosismentioning
confidence: 99%
“…by phytosterols. Brüll et al (2010) demonstrated TLR2 activa-tion in human peripheral blood mononuclear cells by plant stanols and plant sterols. On the other hand, the same authors did not confirm the activation of TLR4.…”
Section: Discussionmentioning
confidence: 99%